Level of energy supplementation in beef cattle grazing Italian ryegrass - Mariana Trindade Barreto; Renata da Rosa Dornelles; Danielli dos Santos Comassetto; Letícia Romani Simoni; Ricardo Pedroso Oaigen; Deise Dalazen Castagnara; Luciana Pötter; Tiago Antonio Del Valle; Eduardo Bohrer de Azevedo (Ciência Rural)
ABSTRACT: This study evaluated the efficiency of use and productive performance of beef cattle on Italian ryegrass (Lolium multiflorum Lam.) pasture supplemented with levels of energy supplementation. The trial was performed in two experiments (years 2019 and 2021) and the experimental design was randomized blocks with five treatments and two replications. The treatments corresponded to levels of supplementation: CON: Pasture without supplementation; MN: Pasture + Mineral Supplementation (commercial product): 80g animal day-1; SE0.1: Pasture + Energy supplement 0.1% BW (commercial product); SE0.5: Pasture + Energy supplement 0.5% BW (commercial product 0.1% + 0.4% rice bran (RB)); SE1.0: Pasture + Energy supplement 1.0% BW (commercial product 0.1% + 0.9% RB). The variables studied were: herbage yield and bromatological composition, average daily weight gain (ADG), stocking rate (SR), weight gain per area (GPA), and the compensation exchange ratio of supplement intake in comparison to gain of weight. The data were submitted to analysis of variance using and compared by the Tukey test at 5%. The ADG data were submitted to regression analysis e segmented regression. GPA and SR showed no significant difference between treatments with levels of energy supplementation. The segmented ADG regression resulted in a break point at a low supplementation level of 0.16% BW. The exchange ratio showed an interaction between treatments and year, showing the influence of the productive and nutritional characteristics of the pasture on the efficiency of supplementation use.